Inhibition of Ralstonia solanacearum by Warburgia ugandensis stem bark and leaf crude extracts obtained using organic solvents (African Journal of Science, Technology and Social Sciences, 2024)
Ralstonia solanacearum is a soil-borne bacterial pathogen that poses significant threat to the Solanaceae family and other crops. It causes widespread bacterial wilt, a devastating disease that affects the plant's water transport system, leading to wilting and death. Numerous chemical agents and treatment methods have been employed in attempts to control R. solanacearum, but are ineffective.  The study aimed to determine the in vitro efficacy of W. ugandensis stem bark and leaf crude extracts against R. solanacearum. W. ugandensis stem bark and leaf crude extracts were obtained using organic solvents viz. methanol, ethanol, dichloromethane and hexane. In vitro, antagonistic activities against R. solanacearum of all organic crude extracts of W. ugandensis were determined by standard agar well diffusion assay on Kelman’s 2, 3, 5- triphenyl tetrazolium chloride medium in triplicates. Two-way analysis of variance (ANOVA) was used in the statistical analysis of the mean diameter inhibition zones. All the organic solvents crude extracts of W. ugandensis were inhibitive against R. solanacearum. However, the stem bark crude extracts exhibited significantly higher efficacy against R. solanacearum compared to the leaf crude extracts.  The crude extracts were subjected to a serial dilution to determine the minimum inhibitory concentration (MIC). W. ugandensis stem bark dichloromethane crude extracts had the lowest MIC of 1 mg/ml. W. ugandensis stem bark dichloromethane crude extracts were most effective against R. solanacearum. Further research is important to determine the bioactive compounds against R. solanacearum in W. ugandensis stem bark dichloromethane crude extracts.
Keywords: Ralstonia solanacearum, crude extracts, Warburgia ugandensis, minimum inhibitory concentration